2018
DOI: 10.3329/jbas.v42i1.37837
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Aquaculture : Importance and Future Guidelines

Abstract: An alternative approach to manage fish health that is fast gaining attention in the aquaculture industry is probiotics, a microbial intervention approach. Probiotics have shown that they can help to increase fish growth by enhancing the feed conversion efficiency, as well as confer protection against harmful bacteria by different modes of action. The present paper shows the current knowledge of the use of probiotics in aquaculture, particularly focusing on their modes of action such as spatial and nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…In the beginning interest was focused on the application of probiotics as growth promoters and to improve the health of animals [4]. Essa et al [16] reported better growth, feed utilization and improved enzyme activities of amylase, protease and lipase in Nile tilapia when diets were supplemented with a probiotic, L. plantarum.…”
Section: Growth Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…In the beginning interest was focused on the application of probiotics as growth promoters and to improve the health of animals [4]. Essa et al [16] reported better growth, feed utilization and improved enzyme activities of amylase, protease and lipase in Nile tilapia when diets were supplemented with a probiotic, L. plantarum.…”
Section: Growth Promotermentioning
confidence: 99%
“…Intensification has come up as a boon to meet the increasing food demand [3]. However, the growth of aquaculture industry where extensive, semi-intensive system transferred into intensive and super-intensive form resulting sudden and onset mortalities, are mainly caused by virulent microorganisms [4,5]. The best way to prevent diseases and commercial losses of fish would be to improve their resistance to infections in addition to improving husbandry with good health management.…”
Section: Introductionmentioning
confidence: 99%
“…Later, a number of other bacteria sp. such as Aeromonas hydrophila, A. media, Altermonas sp, Bacillus subtilis, Carnobacterium inhibens, Debaryomyces hansenii, Enterococcus faecium, Lactobacillus helveticus, L. plantarum, L. rhamnosus, Micrococcus luteus, Pseudomonas fluorescs were also found to be effective for potential application in the aquaculture industry (Al-Mamun et al, 2018) [2] . There are three types of probiotics used in aquaculture, mainly:…”
Section: Probiotics and Its Typesmentioning
confidence: 99%
“…However, little is known about the environmental impact or the side effects of probiotics in animal rearing. Probiotic preparations applied in animal (veterinary) husbandry are used in commercial rearing, and they are introduced directly to aquaculture without considering their future impact [ 24 ]. For this reason, the properties of probiotic bacteria and their influence on the water environment and other aquatic organisms should be investigated before these strains are introduced to fish farms.…”
Section: Introductionmentioning
confidence: 99%